Bond strength model for externally bonded FRP-to-timber interface. (15th September 2018) - Vahedian, Abbas; Shrestha, Rijun; Crews, Keith
Abstract: Despite the large number of studies on externally bonded elements using FRP composites, there is a significant knowledge gap to gain a comprehensive understanding of potential parameters such as bond width, bond length, material properties and geometries that influence bond strength. Behaviour of FRP bonded to concrete has been well investigated and there are a number of experimental and theoretical studies in this area; however, limited attempts have been made to investigate the bond behaviour of the FRP to timber interface. This paper reports an investigation on the behaviour of FRP externally bonded to timber. A novel theoretical model has been developed through stepwise regression analysis of 136 single shear FRP-to-timber joints. This has led to establishing a new predictive model for determination of the bond strength for FRP-to-timber joints. Results of this stepwise regression analysis are then assessed with results of experimental tests, and satisfactory comparisons have been achieved between ultimate applied loads and the predicted loads. Finally, a significant improvement in prediction of bond behaviour has been achieved when results of the proposed analytical model compared with the existing models from the literature, signifying the capability of the new models.